A new strategy of studying protein–protein interactions: Integrated strong anion exchange/reversed‐phase chromatography/immunoprecipitation coupled with mass spectrometry for large‐scale identification of proteins interact with immunoglobulin G in HeLa cells. Issue 20 (11th September 2020) - Qin, Feng; Wang, Xuantang; Yan, Guoquan; Gao, Mingxia; Zhang, Xiangmin
Abstract: Recently, significant research efforts have been devoted to the development of technology for large‐scale analysis of protein–protein interactions. Herein, a comprehensive method by coupling the first‐dimension strong anion exchange chromatography with the second‐dimension reversed‐phase liquid chromatography via immunoprecipitation technique and high‐resolution mass spectrometry analysis was developed for analyzing protein–protein interactions. After two‐dimensional liquid chromatography separation, 108 fractions were obtained in one experiment. Immunoglobulin G from human serum was used as a model of an interacting protein. As a result, 919 proteins in these fractions were identified to interact with immunoglobulin G. By searching STRING database and data analysis, 27 of 919 proteins were inferred to directly interact with immunoglobulin G. Moreover, important target proteins that interacted with immunoglobulin G were mapped in the two‐dimensional liquid chromatography system, which facilitated selection of these proteins from specific fractions. These results demonstrated that the proposed method can be useful for large‐scale investigation of protein–protein interactions and as an advanced tool for the isolation of target proteins.